2016
DOI: 10.14198/raei.2016.29.13
|View full text |Cite
|
Sign up to set email alerts
|

iCap: Intralingual Captioning for Writing and Vocabulary Enhancement

Abstract: The research on the use of active captioning or subtitling in foreign language learning has considerably increased in the course of the last decade, although there is still lack of evidence as regards the potential advantages of intralingual captioning in this context. The present project attempts to fill this void by analysing the didactic use of intralingual subtitling in a distance learning environment both in terms of written production and vocabulary acquisition. To this end, a total number of 41 undergra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
16
0
5

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
2
1

Relationship

2
5

Authors

Journals

citations
Cited by 19 publications
(22 citation statements)
references
References 0 publications
1
16
0
5
Order By: Relevance
“…The study on intralingual subtitling alone reports encouraging results on writing skills enhancement in undergraduate distance learning students of English, who subtitled a sitcom excerpt using ClipFlair (Talaván et al, 2016b).…”
Section: Discussionmentioning
confidence: 97%
See 3 more Smart Citations
“…The study on intralingual subtitling alone reports encouraging results on writing skills enhancement in undergraduate distance learning students of English, who subtitled a sitcom excerpt using ClipFlair (Talaván et al, 2016b).…”
Section: Discussionmentioning
confidence: 97%
“…However, two such studies have been identified. One was carried out by López Cirugeda and Sánchez Ruiz (2013) Talaván et al (2016b) present the findings of a study on intralingual captioning (iCap) for the enhancement of writing skills and vocabulary acquisition. The study was carried out with 41 B1-level undergraduate students of English at UNED, Spain over a month and a half in a distance-learning setting.…”
Section: Intralingual Subtitlingmentioning
confidence: 99%
See 2 more Smart Citations
“…Within iCap, the research team created ten ClipFlair activities i using ten videos taken from the American sitcom How I Met Your Mother (Bays andThomas 2005-2014) and had students working on their intralingual subtitling for two months, with very positive feedback and learning (Talaván et al 2016). Thus, the idea behind iDub rested upon replicating these ten activities but changing the instructions, so that students were asked to record their voices in a dubbing-like manner, as will be explained in the description of the tasks below, instead of creating subtitles.…”
Section: The Idub Projectmentioning
confidence: 99%